Pembongkaran Puitik terhadap Diksi-Diksi Gender dalam Sajak-Sajak Dorothea: Kontra Hegemoni Dunia Penciptaan Kaum Lelaki - Rangga Asmara; Widya Ratna Kusumaningrum (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2018)
In the last two decades, women’s issues have been attracting public attention, particularly for those who see and study women from male world of construction. In the literature framework, the existing problems are not limited to the women’s involvement in the creation, criticism, and as readers only. However, the growth of the creation of female poets has opposed to men's superiority towards women. The role of gender and institution of marriage, which have been the symbol of hegemonic masculinity, has become a deconstruction and parody. The aim of this study is to dismantle the gender dictions in the Dorothea’s poem, which reflect the hegemonic masculinity. The object of this research is the poetry collections entitiled ‘Nikah Ilalang’ by Dorothea Rosa Herliany. Technique of data collection used was notetaking. In analyzing the data, Dorothea's poetries are studied by using heuristic and hermeneutic techniques. In using hermeneutic technique, this study used semiotic approach and potential/actual hypogram in order to find a proper model as matrix actualization.